EFFECT OF INSECURITY ON AGRICULTURAL OUTPUT IN BENUE STATE, NIGERIA - Ijirshar, Victor Ushahemba; Udaah, Isaiah Iortyom; Mile, Bridget Ngodoo; Vershima, Joyce Seember; Adaudu, Abba (Jurnal Ekonomi-Qu, 2025)
This study examined the effect of insecurity on agricultural output in Benue state. A descriptivebsurvey design was employed, and 400 respondents were purposively selected from insecurity-prone localbgovernment areas, namely, Guma LGA, Agatu LGA, Gwer LGA, Gwer-West LGA, Katsina-Ala LGA,bLogo LGA, Ukum LGA and Kwande LGA. The data were collected through the administration of abquestionnaire and were analysed using t tests and structural equation modelling (SEM). The t-test was usedbto compare farmers' incomes before and after the insecurity in the study area to assess if the differencesbwere statistically significant, while Structural Equation Modelling analysed the complex relationships amongbmultiple variables, employing regression and factor analysis to model both direct and indirect effects. Thebresults revealed that the monetary value of crop and livestock output decreased during periods of insecurity.bFurthermore, the study showed that insecurity has an adverse effect on crop and livestock output. Thisbmeans that a one percent increase in insecurity leads to a 0.211% and 0.311% decrease in crop and livestockboutput respectively. The study concluded that insecurity reduced agricultural output in Benue state. Basedbon the findings, it was recommended that the government deploy more security personnel, establishbcommunity policing initiatives, and employ modern surveillance technologies to deter criminal activities inbinsecure areas. Additionally, for places experiencing farmer-herder conflict, the government should providebgrazing reserves for herdsmen and further strengthen the state law on open grazing prohibition and thebestablishment of ranch law.